Effect of hay quality and breed on the onset of puberty and subsequent reproductive performance in beef heifers - R.C. Perry; L.R. Corah; R.C. Cochran; J.R. Brethour (Kansas Agricultural Experiment Station Research Reports, 1988)
The effect of hay quality on the onset of puberty and subsequent reproductive performance was evaluated in 51 3/4 Hereford x 1/4 Angus (HA) heifers and 47 3/4 Hereford x 1/4 Brahman (HB) heifers. Two qualities of alfalfa hay were fed ad libitum. along with an average of 3.1 lbs/hd/day of ground sorghum grain. HB heifers were heavier and carrying more backfat and body condition (P<.05) at the start of the experiment and they maintained their weight advantage through out the experiment. A higher (P<.05) percent of the UB heifers reached puberty by 14 and 15 months of age and became pregnant during a 45 day artificial insemination breeding period. HA heifers reached puberty at a lighter (P<.05) average weight. Heifers fed high quality alfalfa hay were heavier (P<.05) by the start of the breeding season and were carrying more (P<.05) backfat and body condition. A higher percent (P=.08) of the heifers receiving higher quality hay reached puberty by 16 months of age and a higher (P=.10) percent became pregnant during the breeding period. Heifers inseminated at their pubertal estrus had lower (P=.04) first service conception rates than heifers inseminated at their second or later estruses (52% vs. 88%).
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Hay; Puberty; Performance; Heifers